Urban Renewal and Growth Opportunity Barriers of Microenterprises: Between Working Space Scarceness and Incongruity in Shashemene City, Ethiopia - Fanta, Tarekegn Girma; Megento, Tebarek Lika (The ITB Journal Publisher, 2018)
In Ethiopia lack of working space/business premises is one of the external growth opportunity barriers for microenterprises resulting in inefficient absorption of the large labor pool currently entering into this sector of the economy. It also results in sever competition among businesses for city space, leading to street vending and informal business. The overall purpose of this study was to examine the challenges faced by microenterprises pertinent to shortage of working space. A total of 564 samples (304 and 260 enterprise in old but transformed buildings and newly built buildings in the city, respectively) were selected using simple random sampling. For this particular study an embedded mixed research design (EMRD, one methodology within another one) was applied. The data were collected using a survey questionnaire, GIS and interviewes. The obtained quantitative data were analyzed using SPSS version 20 and qualitative techniques, description and narration. The findings presented in this paper show the prevalence of working space scarceness and incongruity in Shashemene city. Thus, it can be suggested that the city need to revisit urban land leasehold proclamation performance, urban renewal initiative progress, and old business premisesâ transfer procedures, and also integrate local trade unions/chambers of commerce synergy and firmsâ growing working space demand.Keywords. Urban, renewal, microbusiness, working space.Abstract. Di Etiopia, kurangnya ruang kerja/tempat usaha menjadi salah satu hambatan peluang pertumbuhan eksternal bagi usaha-usaha mikro yang mengakibatkan penyerapan yang tidak efisien akan tenaga kerja yang besar yang saat ini masuk ke sektor ekonomi. Hal ini juga mengakibatkan persaingan yang ketat di antara bisnis akan ruang kota yang mengarah ke penjual jalanan dan bisnis informal. Tujuan keseluruhan dari penelitian ini adalah untuk melihat tantangan yang dihadapi oleh usaha-usaha mikro yang berkaitan dengan kurangnya ruang kerja. Ukuran sampel sejumlah 564 (304 dan 260 transaksi di gedung-gedung tua tetapi diubah dan bangunan yang baru dibangun di kota masing-masing) dipilih menggunakan teknik acak sederhana. Khusus untuk studi ini, diterapkan Embedded Mixed Research Design (EMRD, satu metodologi yang terletak di dalam yang metode riset yang lain. Data dikumpulkan menggunakan survei kuesioner, GIS dan wawancara. Data kuantitatif yang diperoleh dianalisis menggunakan SPSS versi 20 dan teknik analisis data kualitatif, deskripsi dan narasi. Temuan yang disajikan dalam artikel ini, menunjukkan bahwa ruang kerja di Shashemene memiliki prevalensi langka dan tidak sesuai. Dengan demikian, dapat disarankan kota tersebut meninjau kembali kinerja proklamasi sewa lahan perkotaan, kemajuan inisiatif pembaharuan perkotaan prosedur transfer tempat usaha lama dan juga mengintegrasikan sinergi antara serikat pekerja/ruang perdagangan lokal dan permintaan akan ruang kerja yang meningkat.Kata Kunci. Urban, pembaruan, bisnis mikro, ruang kerja.